2009
DOI: 10.1007/s11626-008-9164-3
|View full text |Cite
|
Sign up to set email alerts
|

Dihydro-alpha-lipoic acid has more potent cytotoxicity than alpha-lipoic acid

Abstract: Alpha-lipoic acid has been shown to possess cancer-cell-killing activity via activation of the apoptosis pathway. In this study, the cytotoxic activities of alpha-lipoic and dihydro-alpha-lipoic acid were compared in HL-60 cells. The cell-killing activity of dihydro-alpha-lipoic acid was higher than that of alpha-lipoic acid. Both alpha-lipoic and dihydro-alpha-lipoic acid induced caspase-3 cleavage and internucleosomal DNA fragmentation in treated cells. On the other hand, apparent necrotic or late-stage apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
(26 reference statements)
2
12
0
1
Order By: Relevance
“…In support of our results, long time exposure to ALA results in increase of lipid peroxidation, mitochondrial damage and inhibition of glycogen synthesis [17,36]. Also, it has been shown that high dose of ALA could arrest cell cycles in some cells [35,55] or could provoke cell death through internucleosomal DNA fragmentation and caspase cleavage in numerous cancer cell lines [48,55,57]. Hence, it appears that high doses of ALA more than 100 uM are toxic for isolated preantral follicles.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In support of our results, long time exposure to ALA results in increase of lipid peroxidation, mitochondrial damage and inhibition of glycogen synthesis [17,36]. Also, it has been shown that high dose of ALA could arrest cell cycles in some cells [35,55] or could provoke cell death through internucleosomal DNA fragmentation and caspase cleavage in numerous cancer cell lines [48,55,57]. Hence, it appears that high doses of ALA more than 100 uM are toxic for isolated preantral follicles.…”
Section: Discussionsupporting
confidence: 84%
“…This observation may give explanation about our finding which why increasing of ALA concentrations results in decrease developmental competence of isolated follicles. In addition, as previous mentioned, high dose of ALA in numerous cancers cell lines could induce apoptosis [35,48,55,57] which explicates, high degeneration rate of follicles in the presence of high concentrations of ALA.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our previous data showed internucleosomal DNA fragmentation as one of the features of apoptosis in HL-60 cells 23 . In the present study, an increase in the sub-G1 population was observed Fig.…”
Section: Figmentioning
confidence: 91%
“…Последние исследования сообщают о её противоопухолевых эффектах [3][4][5][6][7]. ЛК образуется в организме и присутствует в следовых количествах.…”
unclassified